Vom Text zur Übung. Kollokationen in Lesetexten und ihre Widerspiegelung in Übungen (am Beispiel ausgewählter DaF-Lehrwerke) - Targońska, Joanna (Linguistik Online, 2018)
Collocations are an important part of lexis. Their use is often indispensable and they cannot be replaced by any other lexical means. Unfortunately, they pose a big problem for learners of a foreign language because they are not conspicuous and the learners are not aware of their conventionality and fixed character. It is then important to draw the learner’s attention to that part of lexis, for example by placing collocations in the vocabulary practice. This analysis attempts to investigate to what degree the lexical practice following specific texts in a coursebook incorporates the collocations that have been used in those texts. The analysis focuses on the coursebooks for German as a foreign language for learners at B1+ level. The objective of the analysis is to check if the students’ attention is directed to collocations in the texts themselves and then if the collocations are part of the vocabulary practice. The research concerns the degree to which the collocations in the texts become part of the vocabulary practice (quantitative analysis) and their quality (qualitative analysis).